Impact of various foot arches on dynamic balance and speed performance in collegiate short distance runners: A cross-sectional comparative study - Sudhakar, Selvaraj (J Orthop, 2018)
OBJECTIVE: To compare the impact of foot arches on dynamic balance and speed performance. MATERIALS AND METHODS: 30 collegiate male short distance runners were divided into three groups based on foot arches, high, neutral and low. Balance and speed performance were estimated based on scores of star excursion balance test (SEBT), 40 yard dash test and vertical jump test (VJT). RESULTS: Significant improved scores (p < 0.001) were noted in SEBT, 40 yard dash test and VJT. CONCLUSION: Short distance runners with high arch foot have improved dynamic balance and speed when compared to low and neutral arch foot.